Relationship between Serum Vitamin D Level and Gestational Diabetes Mellitus in Patients Referring to Imam Hossein Hospital in Tehran, Iran, during 2015 - Maryam Sadat Hosseini; Elina Bairamzadeh; Ali Reza Dadashi; Shahnaz Fatahi; Ebadallah Shiri Malekabad (Mashhad University of Medical Sciences, 2018)
Introduction: Gestational diabetes is one of the most important abnormalities occur over the 24 weeks of gestation. The recognition of the gestational diabetes factors can play an important role in the improvement of the pregnancy condition; therefore,this study was to investigate the relationship between serum vitamin D level and gestational diabetes mellitus in patients referred to Imam Hossein Hospital in Tehran, Iran, during 2015. Materials and Methods: In this cross-sectional study was conducted on 164 pregnant women in Tehran during 2015. Patients were tested for gamma-glutamyl transferase using a oral glucoseof 50 g and then a 3-hour glucose tolerance test was used. Individuals with diabetes mellitus were considered case group and individuals without gestational diabetes mellitus (control group). Blood samples were taken to determine and compare serum vitamin D level between the two groups. The data were analyzed using SPSS (version 21) through the Chi-square and independent t-test. Results: The mean values of 25-hydrozxy-vitamin D level were 29.4±19 and 24.13±13.3 in the case and control groups, respectively.  In this regard, the results of independent t-test revealed a significant difference between the two groups  (P=0.042). Moreover, the ROC curve analysis of vitamin D with a cut point of 20 indicated a sensitivity level of 53% and a specialty of 45%. Based on the results of this study, pregnant women with vitamin D deficiency are twice at risk of developing gestational diabetes, compared to their healthy counterparts. Conclusion: The low level of serum vitamin D is the independent risk factor for gestational diabetes mellitus. However, due to the limitations of this study it is essential to conduct further evaluations.